2023
DOI: 10.3390/nano13020320
|View full text |Cite
|
Sign up to set email alerts
|

The Photocatalytic Conversion of Carbon Dioxide to Fuels Using Titanium Dioxide Nanosheets/Graphene Oxide Heterostructure as Photocatalyst

Abstract: Carbon dioxide (CO2) photoreduction to high-value products is a technique for dealing with CO2 emissions. The method involves the molecular transformation of CO2 to hydrocarbon and alcohol-type chemicals, such as methane and methanol, relying on a photocatalyst, such as titanium dioxide (TiO2). In this research, TiO2 nanosheets (TNS) were synthesized using a hydrothermal technique in the presence of a hydrofluoric acid (HF) soft template. The nanosheets were further composited with graphene oxide and doped wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…For TNS, the spectra reveal peaks at 25.63, 38.20, 48.30, 54.10, 55.30, 62.90, 68.93, 70.44, and 75.28°, which are indexed to the {101}, {004}, {200}, {105}, {211}, {204}, {116}, {220}, and {215} planes of TiO 2 anatase (PDF: 00-064-0863). 7 . The shift can be attributed to replacing TiO 2 oxygen with amine nitrogen, which leads to a partial N-dope interaction on TiO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For TNS, the spectra reveal peaks at 25.63, 38.20, 48.30, 54.10, 55.30, 62.90, 68.93, 70.44, and 75.28°, which are indexed to the {101}, {004}, {200}, {105}, {211}, {204}, {116}, {220}, and {215} planes of TiO 2 anatase (PDF: 00-064-0863). 7 . The shift can be attributed to replacing TiO 2 oxygen with amine nitrogen, which leads to a partial N-dope interaction on TiO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8 Our research group has demonstrated the use of TiO 2 /GO composites for CO 2 photoreduction in the aqueous phase 8,9 and gas phase. 7 We studied the effects of transition metal doping 8 and reported excellent photoactivity of copper-doped TiO 2 /GO composites. We demonstrated that the 2D−2D heterostructure composites gave outstanding photoactivity due to excellent electron−hole separation and sufficient engagement from active radicals at the n−p interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 photocatalysts treated at 800 °C in hydrogen atmosphere for 1 h showed higher visible photocatalytic activity for C-H/C-H coupling of dipyrromethanes with azines than commercial TiO 2 (P25) [ 16 ]. TiO 2 nanosheets were proved to exhibit superior photocatalytic activity for CO 2 reduction than the nanoparticle, thanks to its much higher surface area and surface activity [ 17 ]. In addition, the effects of the particle size of TiO 2 on photocatalytic pollutant removal were thoroughly investigated by Kim et al [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of fossil fuels produces large amounts of CO 2 and increases the concentration of CO 2 in the atmosphere, which causes a series of serious environmental problems. Using photocatalysts to convert CO 2 into organic products through solar energy is one of the best ways to solve this problem, like killing two birds with one stone to save our environment. Various photocatalysts have been explored, including semiconductor materials such as TiO 2 , Zn 2 GeO 4 , ZnGa 2 O 4 , etc.…”
Section: Introductionmentioning
confidence: 99%